FAMILY MEDICINE IN UNDERGRADUATE MEDICAL CURRICULUM: A COST-EFFECTIVE APPROACH TO HEALTH CARE IN PAKISTAN - Iqbal, Saima P. (Journal of Ayub Medical College Abbottabad, 2010)
Background: Shifa College of Medicine introduced a two-week rotation in Family Medicine for their third-year medical students in 2008. The purpose of this study was to determine what impact it made on students and how many would consider becoming Family Physicians in future. Methods: A questionnaire-based prospective study conducted at Shifa College of Medicine, Islamabad during academic year 2008. Results: A total of 46 students rotated in Family Medicine throughout the academic year-2008. Fifteen students were aware of Family Medicine as a specialty prior to starting their rotation, and only 3 expressed an interest to pursue Family Medicine as a future career. At the start of the rotation only 15 students were able to give correct definition of Family Medicine and on questioning whether it should be a part of the undergraduate curriculum, only 24 answered yes while the rest were unsure. After the rotation, a significant number of students (37%; p<0.01) considered having a career in Family Practice, and 80% (n=37) were able to give correct definition of Family Medicine as a humanistic approach of medicine with aim to prevent, treat and rehabilitate. About its utility in the undergraduate curriculum, 44 (96%) students believed it should be a regular feature in their curriculum, while 30 (65%) students agreed that their outlook towards patient care had changed. When asked what they learnt most during the rotation, students quoted empathy and development of communication skills. Conclusion: Family medicine rotation as part of undergraduate medical curriculum may help in fostering an interest among medical students in this newly emerging subspecialty which could have a profound effect on delivery of quality health care in this country. Keywords: Undergraduate medical curriculum, Family Medicine, health care, medical education.